The anti-tumor function of aryl hydrocarbon receptor expressed on macrophages in colorectal cancer - 오서희 (The Graduate School, Ajou University, 2024)
Colorectal cancer remains a pressing global health concern, necessitating innovative therapeutic approaches. Macrophages, critical components of the tumor microenvironment, play pivotal roles in immune responses and tumor progression. The aryl hydrocarbon receptor (AhR), also known as environmental sensors, is a transcription factor that depend on ligand binding for activation. It has been implicated in regulating various immune responses. However, its precise role in colorectal cancer-associated macrophages remains unclear. This study aims to investigate the anti-tumor function of AhR expressed on macrophages in colorectal cancer. This study aimed to investigate the anti-tumor function of AhR expressed in macrophages in colorectal cancer. In this study, we demonstrated that AhR expressed in macrophages has an anti-tumor function by suppressing the expression of tumor- related factors in vivo. Macrophage-specific AhR-deficient mice displayed a higher number of tumor nodules, increased weight loss, and reduced survival rates in AOM/DSS-induced colorectal cancer. Additionally, AhR-defective bone marrow- derived macrophages exhibited enhanced level of pro-inflammatory cytokines than wild type, upon differentiation into inflammatory macrophages. Furthermore, macrophage-specific AhR-deficient mice exhibited a more severe inflammatory phenotype and elevated expression of tumor-related factors such as MMP-2, TGF-β and VEGF in colon tissue under DSS-induced colitis. Leveraging TCGA data analysis, we identified a significant correlation between macrophages and STAT3 signal in humans. The results offer evidence supporting the significance of AhR expressed on macrophages in suppressing tumor-related pathways. This study has the potential to suggest AHR in macrophages as a new target for colorectal cancer treatment.
학위논문(석사)--약학과,2024. 2
Keywords: AOM/DSS; Anti-tumor immunity; Aryl hydrocarbon receptor (AhR); Colorectal cancer; Macrophages